Interpretasi Kepuasan Konsumen Terhadap Pelayanan Obat Tanpa Resep Terhadap Kepuasan Konsumen - Nurwulan Adi Ismaya; Siti Novy Romlah; Rofiqo Syafa’a Fatulloh; Tri Okta Ratnaningtyas; Nur Hasanah (STIKes Kharisma Persada, 2020)
Satisfaction is a Function of Performances And Expectations. These research aim to determine the level of customer satisfaction with drug services without a prescription at the Pharmacy K-24 Raya Puspitek and Identifying the level of patient satisfaction by distributing 5-dimensional questionnaires, they are : reliability, responsiveness, assurance, empathy, and tangibility. There are 100 respondents.The questionnaire was distributed based on education and gender. The result showed there are 73% male and 27% female from 100 respondents. While respondents based on undergraduate education as much as 34% which is greater than the others. The result of customer satisfaction found 54% satisfied in Reliability, 47,5% satsified in Responsiveness, 53% satisfied in Emphaty, 49,5% satisfied in Assurance, 53,5% satisfied in Tangible.Overall Pharmacy service quality in K-24 Raya Puspitek Pharmacy is in good or satisfy level.